2014
DOI: 10.1186/1756-0500-7-461
|View full text |Cite
|
Sign up to set email alerts
|

No association found between the detection of either xenotropic murine leukemia virus-related virus or polytropic murine leukemia virus and chronic fatigue syndrome in a blinded, multi-site, prospective study by the establishment and use of the SolveCFS BioBank

Abstract: BackgroundIn 2009, a retrospective study reported the detection of xenotropic murine leukemia virus-related virus (XMRV) in clinical isolates derived from individuals with chronic fatigue syndrome or myalgic encephalomyelitis (CFS). While many efforts to confirm this observation failed, one report detected polytropic murine leukemia virus (pMLV), instead of XMRV. In both studies, Polymerase Chain Reaction (PCR)-based methods were employed which could provide the basis for the development of a practical diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The original study was designed to evaluate the role that methodological approaches had in the previously identified, and now largely rejected, association between xenotropic murine leukemia virus and ME/CFS [32]. The data was collected between June and August 2010.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original study was designed to evaluate the role that methodological approaches had in the previously identified, and now largely rejected, association between xenotropic murine leukemia virus and ME/CFS [32]. The data was collected between June and August 2010.…”
Section: Methodsmentioning
confidence: 99%
“…Participants with ME/CFS also had to have post-exertional malaise lasting >24 hours and significant cognitive impairment in short-term memory and concentration. The final sample included 240 ME/CFS patients who were recruited from four clinical sites as previously report by Irbeck et al [32]. A total of 88 healthy individuals were recruited for the control group, who were matched to ME/CFS patients by zip code (excluded if they lived within the same household), age, sex, and race.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the earlier positive findings were based on laboratory contamination [ 136 140 ]. Studies have shown that commercial reagents and clinical samples could be contaminated with MLV-related virus genomic sequences containing murine DNA, and cloned or amplified XMRV DNA might be the source of contamination.…”
Section: Retrovirusesmentioning
confidence: 99%
“…We considered whether a subset of patients with ME/CFS may exhibit serologic markers associated with NCWS, which might explain some of the corresponding symptoms. We screened serum samples from 131 patients with ME/CFS and 86 healthy controls (table 1), recruited as previously described,9 for the same markers as those in the above-mentioned study on NCWS 1. Questionnaires were used to assess GI symptoms within the past 6 months, including abdominal pain, bloating and nausea.…”
mentioning
confidence: 99%